True Places : A Lowcountry Preacher, His Church, and His People - Lanzano, Stanley F. (Book collections on Project MUSE., 2009)
This book is a documentary photographer's study of the daily and spiritual lives of an African American coastal community. The book contains an emotionally-charged photographic documentary of the lives of evangelical pastor Floyd Knowlin and his close-knit African American congregations who live, work, and worship in a rural stretch of coastal South Carolina. For more than a decade, the photographer immersed himself in the daily practices of this community in Williamsburg and Georgetown counties, befriending Reverend Knowlin and becoming a welcomed part of his extended church family. The respectful relationship that the photographer has forged with his subjects and the trust that they have extended to him shines through in the eighty-three black-and-white and eight color photographs included here, illustrating a vibrant coastal subculture rarely witnessed by outsiders. Many of the photographs document services and church revivals, conveying the great joy, sorrow, and fervor of these meetings while highlighting Knowlin's captivating persona. The photos also provide glimpses into baptisms in the murky, still waters of lowcountry South Carolina rivers. Beyond the church, this book takes us into the private homes and lives of Knowlin's flock, many of whom are of Gullah descent and keep elements of this heritage alive in their daily practices. Collectively these images show a society in transition, where pain and grief are juxtaposed with redemption and bliss. The photographer's narrative of his meeting Reverend Knowlin and his continuing relationship with Knowlin's community is a tale of self-discovery. It is also a testament to the power of faith in the lives of often forgotten South Carolinians. It is a rarity for a photographer to be granted such unlimited access into these communities. Through these images, the photographer creates with the utmost reverence and respect a powerful record of the hardships and hopes he witnessed among Knowlin's congregations to preserve their legacy and to share their inspirational attitude toward life in these true places.--publisher's description.